The 9-item Concise Health Risk Tracking – Self-Report (CHRT-SR9) measure of suicidal risk: Performance in adult primary care patients - Nandy, Karabi; Rush, A. John; Carmody, Thomas J.; Mayes, Taryn L.; Trivedi, Madhukar H. (Frontiers in Psychiatry, 2023)
Purpose: To evaluate the psychometric properties of a 9-item Concise Health Risk Tracking Self-Report (or CHRT-SR9) to assess suicidal risk in adult primary care outpatients. Methods: Overall, 369 adults completed the original 14-item version of CHRT-SR at baseline and within four months thereafter, from which the CHRT-SR9 was extracted using multigroup confirmatory factor analysis. Measurement invariance (across age and sex) and classical test theory characteristics of the CHRT-SR9 were evaluated. Concurrent validity was assessed by comparing CHRT-SR9 responses to those of the suicide item in the Patient Health Questionnaire (PHQ-9), both cross-sectionally and as a change measure over time. Results: Confirmatory factor analysis identified the CHRT-SR9 as the optimal solution. Factors included pessimism, helplessness, despair (2 items each) and suicidal thoughts (3 items). Measurement invariance held across sex and age groups, indicating that mean differences among sub-groups were real and not attributable to measurement bias. Classical test theory revealed acceptable item-total correlations overall (0.57-0.79) and internal consistency (Spearman-Brown from 0.76 - 0.90). Concurrent validity analyses revealed that the CHRT-SR9 can measure both improvement and worsening of suicidality over time. A PHQ-9 response of 0, 1, 2, and 3 on the suicide item corresponded to 7.82 (5.53), 16.80 (4.99), 20.71 (5.36), and 25.95 (7.30) (mean and SD) on CHRT-SR9 total score, respectively. Conclusion: The CHRT-SR9 is a brief self-report evaluating suicidality with excellent psychometric properties that is sensitive to change over time.